Teacher's Strategy in Integrating Character Values in Ma'had Tahfidz Quran Al-Uswah Village, Kuala Langkat District - Haidir Haidir; Yumita Anisa Putri; Lesnida Lesnida; Adi Syahputra (Budapest International Research and Critics University, 2021)
The implementation of character education in Ma'had which is full of noble values in its existence has succeeded in shaping the attitudes and behavior of santriwan and santriwati which are expected to have good character, through the application of a distinctive teacher strategy capable of realizing religious human resources. Ma'had Tahfidz Kampung Qur'an is a non-formal institution that pays attention to strengthening character education, especially religious values, honesty, discipline, and hard work. It is hoped that this value will become an icon that can become a foothold for value transfer so that the vision and mission which is expected to be able to create religious human resources and always interact with the Koran towards the person of Insan Kamil. This research uses qualitative research with a phenomenological approach and descriptive methods. Data collected through observation, interviews, and document study. Data analysis techniques by means of data reduction, data presentation, examination of conclusions and verification. The results of this study are (1) the teacher's strategy in integrating character values for students and students in ma'had (2) the impact of character values for students and students in ma'had through religious, honesty, discipline, and working, (3) Supporting factors and inhibiting Character values for santriwan and santriwati through religion, honesty, discipline, and hard work.